Pengaruh Kecepatan Aliran Udara terhadap Dew Point Effectiveness (DPE) Pada Sistem Maisotsenko Cycle Indirect Evaporative Cooling Ventury dengan Aliran Udara Parallel - Situmeang, Alfrede Elia Jhonson; Wijaksana, Hendra; Astawa, Ketut (Teknik Desain Mekanika; Vol 13 No 2 (2024): April 2024 : Teknik Desain Mekanik, 2024)
Abstract Clean energy is a basic human need. Most existing energy consumption and production systems are inefficient and can damage the environment. Evaporatilve coolinlg is an alternatilve way of mechaniclal vapolr compression lfor air conlditioning appllications. The Maisotsenlko Cyclle (Ml-Cycle) is thle principle of evaplorative coolingl and is recognized as a development of the well-known IEC (Indirect Evaporative Cooling) technology by pre-cooling secondary airflow before entering the secondary air duct. Tlhe main olbjective of tlhis research isl to deterlmine the efflect ofl air velocity variation on Dew Point Effectiveness (DPE). In lthe maisotsenklo cycle indirlect evaporlative cololing ventury system with horizontal parallel flow with air flow velocity variations of l5 m/ls, 7 ml/s, andl 9 m/ls. From the tests conducted, it was found that thle highlest Dew Point Effectiveness occurred at the highlest airl flowl velocity of 5 lm/s, which amounted to 29.8%. Keyword: M-Cycle, DPE, Airflow Velocity